The Valency Structure Of English And Tatar Verbs Of Motion In The Comparative Aspect - Radikovna Sakaeva, Liliya (2019)
The theory of valency is one of the most important topics of modern linguistics. The valency analysis is directly related to the practice of teaching and learning languages in linguistics.The given research is aimed at considering the valency structure of Tatar and English verbsof motion. The relevance of the topic is determined by its general theoretical significance. The comprehensive study of the valency structure of Tatar and English verbs makes a significant contribution to the study of the theory of semantic syntax of these languages. The choice of verbs of motion is also not accidental. The versatility of the semantic structure of this group of verbs takes the first place among other thematic groups.The scientific novelty of the research is that it conducts the comparative study of valency properties and variants of Tatar and English verbs of motion. The work involves experiencing the comprehensive study of valency properties of the main lexico-semantic group of verbs: verbs of motion. Due to the fact that it is impossible to describe in detail all the lexical-semantic groups of verbs within the framework of one study, we limited ourselves to considering the main thematic group – the verbs of motion.